2018
DOI: 10.1038/s41598-018-27321-4
|View full text |Cite
|
Sign up to set email alerts
|

The level of ROCK1 and ROCK2 in patients with pulmonary hypertension in plateau area

Abstract: Pulmonary hypertension (PH) is defined as the mean pulmonary artery pressure (mPAP) ≥25 mmHg under the sea level in resting state. ROCK1 and ROCK2 can be combined to cause the damage of vascular endothelial function. To explore the differences of ROCK1 and ROCK2 in subjects with pulmonary hypertension or normal pulmonary artery pressure in plateau area, and to further understand the mechanism of Rho/rho-kinase pathway activation for promoting pulmonary hypertension, we collected 64 patients with pulmonary hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Two homologous isomers of ROCK exist: ROCK1 and ROCK2 ( Wang et al, 2019 ). The research showed that the activity of ROCK increases in patients with PAH, heart failure, hypertension, and stable angina pectoris ( Liu et al, 2018 ). ROCK is also implicated in the progression of various diseases such as HPH.…”
Section: Discussionmentioning
confidence: 99%
“…Two homologous isomers of ROCK exist: ROCK1 and ROCK2 ( Wang et al, 2019 ). The research showed that the activity of ROCK increases in patients with PAH, heart failure, hypertension, and stable angina pectoris ( Liu et al, 2018 ). ROCK is also implicated in the progression of various diseases such as HPH.…”
Section: Discussionmentioning
confidence: 99%
“…Both ROCK1 and ROCK2 were expressed in early mouse embryos, and the developing heart highly expressed ROCK1, while ROCK2 was continuously expressed during cardiac development [18]. Studies have shown that ROCK genes play an important role in the regulation of apoptosis in animal disease models and various cell types [19][20][21][22][23]. In the rat model of ischemia-reperfusion injury, the expression of Ras homolog gene family, member A, and the activity of ROCK were increased.…”
Section: Discussionmentioning
confidence: 99%
“…Four hundred forty-one potential target genes were predicted by TargetScan and miRDB, as shown in Figure 5a. Through searching relative studies, it was found that ROCK2 is closely related to myocardial damage [14][15][16][17][18][19][20][21][22][23]. There are multiple potential binding sites for miR-133a-5p and the 3′UTR conserved region of ROCK2, as shown in Figure 5b.…”
Section: Prediction Of Mir-133a-5 Target Genementioning
confidence: 99%
“…The red blood cell distribution width (RDW) is a parameter that variability and heterogeneity in reflects red blood cell size [ 10 ]. RDW has been recognized as a potential independent risk factor for ischemic cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%